Boosting Carry with Equilibrium Exchange Rate Estimates - Michał Rubaszek; Joscha Beckmann; Michele Ca' Zorzi; Marek Kwas (Open Economies Review, 2024)
We construct currency portfolios based on the premise that exchange rates gradually converge toward their equilibrium levels, yielding three key findings. First, this convergence can be leveraged to build profitable portfolios. Second, the slow rate of convergence over shorter horizons aligns with the sustained profitability of carry trade strategies, where investors borrow in low-yield currencies and invest in high-yield ones. Third, incorporating the predictive insights of equilibrium exchange rates can boost the performance of carry trade strategies.
Keywords: F31; G12; G15; 330; Equilibrium exchange rate; Carry trade; Trading strategies